PROFIL SERUM AMYLOID A PADA PASIEN SINDROM KORONER AKUT DI RSUP DR. SARDJITO YOGYAKARTA Kajian pada Pasien Unstable Angina Pectoris, Non- ST Elevation Myocardial Infarction dan ST Elevation Myocardial Infarction - , Yusnitasari, dr. Setyawati, Sp-PK(K) ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Acute coronary syndrome is a major health problem, and one of the most common cause of mortality worldwide, as approximately one third of all death in 2001 was caused by cardiovascular disease. It is estimated that in 2020, there will be 25 millions of death annually as the result of cardiovascular disease and almost half of will be caused by coronary heart disease. Serum amyloid A (SAA) protein is an acute phase protein that is produced by the liver, in response to acute and chronic inflammatory stimuli and its level can reach as high as 1000 fold. Serum Amyloid A attenuate HDL performance by replacing Apo A1 as the major protein of HDL. Objective : to assess the level of serum amyloid A level in patients with UAP and NSTEMI and STEMI in Dr. Sardjito Hospital Yogyakarta. Method: This is a cross sectional study, with as many as 60 subjects will be entered in the study from Dr. Sardjito Hospital, Yogyakarta. These subjects are the patients with UAP, NSTEMI and STEMI, with documented electrocardiography and cardiac enzyme measurement. Meanwhile, SAA will be measured with sandwich ELISA method. The subjectâs characteristic data will be presented as the result from descriptive analysis. The mean of SAA level in UAP, NSTEMI and STEMI will be compared. The difference of means will tested with t- or Mann-Whitney and ANOVA or Kruskall Wallis with significance level of p<0,05 and 95% confidence interval. Result: There are significance differences in median SAA levels between UAP (77.47 ng/mL) and NSTEMI patients (123.29 ng/mL), in which p = 0.001 and between UAP with STEMI patients (131.12 ng/mL) and p = 0.001. But not significance differences in median SAA levels between NSTEMI and STEMI, in which p=0.056. There was a moderate correlation between SAA level and troponin I in NSTEMI (r=0.482, p=0.032) and STEMI patients (r=0.568, p=0.009). There were two subjects of NSTEMI with normal troponin I levels (<0,1ng/mL) at ER admission but high SAA levels, 118.40 and 112,76 ng/mL, respectively. At the second measurement of troponin I, we found elevated troponin I levels by 1.02 and 0.18ng/mL, respectively. Conclusion: There is significant differences in SAA levels between UAP with NSTEMI patients and UAP with STEMI patients, in which p=0.001. Positive correlation was found between SAA and troponin I in NSTEMI and STEMI.